Molecular half-full mechanisms by phagocityc cells on invasive Aspergilosis (Colombia Medica, 2012)
Fungus from the Aspergillus genus mainly affects lung tissue, occurring when the integrity of the host immune system is compromised. The human body uses immunocompetence conditions from mechanical and enzymatic defenses and the action of the innate immune system cells and also uses adaptive responses to control infection. Neutrophils, macrophages, and dendritic cells are critical as antifungal effector cells possess surface receptors that recognize fungal structures and trigger specific responses. TLRs and Dectin-1 the most studied for this interaction. TLRs are responsible for the production and release of cytokines and Dectin-1 is essential in the phagocytosis of the particle recognition and production of ROS. The best-studied cytokines and its crucial role in the response to Aspergillus spp. are TNF-α, IFN-γ, and IL-12. In this work, we reviewed the main mechanisms related to molecular receptors on phagocytic cells involved in the recognition of Aspergillus spp. Understanding the immune response in situations of  immunocompetence and its comparison in immunodeficient organisms could provide alternatives to control invasive aspergillosis.